1998
DOI: 10.1002/(sici)1097-4652(199812)177:4<507::aid-jcp2>3.0.co;2-k
|View full text |Cite
|
Sign up to set email alerts
|

Signal transduction pathways in the mitogenic response to G protein-coupled neuropeptide receptor agonists

Abstract: Neuropeptides, including mammalian bombesin-like peptides, act as potent cellular growth factors and have been implicated in a variety of normal and abnormal processes, including development, inflammation, and malignant transformation. These signaling peptides exert their characteristic effects on cellular processes by binding to specific G protein-coupled receptors (GPCR) on the surface of their target cells. Typically, the binding of a neuropeptide to its cognate GPCR triggers the activation of multiple sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
97
0
6

Year Published

2000
2000
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 160 publications
(105 citation statements)
references
References 96 publications
2
97
0
6
Order By: Relevance
“…Numerous studies have demonstrated that a rapid increase in the tyrosine phosphorylation of the non-receptor tyrosine kinase FAK is a prominent early event in cells stimulated by multiple signaling molecules that regulates cell proliferation, migration, and apoptosis [3,6,52]. On the contrary, much less is known about the regulation of FAK phosphorylation at serine residues by external stimuli including GPCR agonists and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that a rapid increase in the tyrosine phosphorylation of the non-receptor tyrosine kinase FAK is a prominent early event in cells stimulated by multiple signaling molecules that regulates cell proliferation, migration, and apoptosis [3,6,52]. On the contrary, much less is known about the regulation of FAK phosphorylation at serine residues by external stimuli including GPCR agonists and growth factors.…”
Section: Discussionmentioning
confidence: 99%
“…[Ca 2Ļ© ] i in IEC-18 cells. The mobilization of Ca 2Ļ© from intracellular stores leading to a rapid and transient increase in [Ca 2Ļ© ] i is one of the earliest events stimulated by the binding of agonists to GPCRs that signal through G q -mediated activation of PLC (5,20,66). To identify the expression of G q -coupled GPCRs in intestinal epithelial cells, multiple peptide hormones were screened for their ability to induce Ca 2Ļ© mobilization in IEC-18 cells, a nontransformed intestinal epithelial cell line derived from rat ileum (56,57 There are at least three GPCR subtypes that bind AVP, namely, V 1A , V 1B , and V 2 receptors (6).…”
Section: Methodsmentioning
confidence: 99%
“…The two best characterized isoforms, ERK-1 (p44 mapk ) and ERK-2 (p42 mapk ), are directly activated by phosphorylation on specific tyrosine and threonine residues by the dualspecificity ERK kinase (or MAPK kinase; MEK) (83). In some cell types, activation of Pyk2 and Src family kinases triggers the stimulation of the Raf-MEK-ERK cascade via Ras activation (30,66).…”
Section: Avp Induces a Rapid And Transient Increase Inmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect depended on substrate concentration. (J Am Soc Mass Spectrom 2007, 18,[1925][1926][1927][1928][1929][1930][1931]) Ā© 2007 American Society for Mass Spectrometry P rotein phosphorylation is one of the most important post-translational modifications, as it regulates cellular functions through information processing [1][2][3]. In this context, the determination of phosphorylated peptides using mass spectrometry has attracted much attention in many biological and pharmacological fields.…”
mentioning
confidence: 99%